The Influence of Using Canva-Based Video Learning Media on Learning Outcomes in Work and Simple Machines Material - Patricia Sasmita Kadir; Supartin Supartin; Abdul Haris Odja; Trisnawaty Junus Buhungo; Lukman Samatowa; Raghel Yunginger (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The demands of 21st-century learning require the integration of digital and interactive media, as conventional science instruction often fails to optimally engage students and improve learning outcomes. The study aims to investigate the impact of using Canva-based video learning media on students' learning outcomes in the topic